Commodities: Factors affecting pricing of Gold in relation to other metals - Somaya, Bianca (2009)
This paper looks at the prices of Gold, silver, platinum and palladium for a time period from 1990 till 2008, a good twenty years almost and an analysis is conducted to see if there is a relationship between these metals. To see if these precious metals have significant changes in relation to changes in gold prices has been statistically tested. Factors that affect gold and such commodities are also mentioned and a more in depth knowledge into the world of these metals has been stated. I have used Cointegration tests for this comparison as it is part of time series data, and a further vector error correction model test has been conducted. This paper hopes to give one a view of whether gold is a good investment and why so, also if other precious metals can be considered as lucrative investment options. Gold has always been a safe haven and many studies have been done on the same but gold’s effect on other metals has not been largely dealt with.